Intensive Supervision Programs and Recidivism: How Michigan Successfully Targets High-Risk Offenders - DeVall, Kristen E. (The prison journal, 2017)
The United States has witnessed enormous criminal justice system growth in the past 60 years. In response to calls for reform, several jurisdictions have implemented programs that provide intensive supervision for high-risk offenders, swiftly responding to violations with sanctions. This quasi-experimental study is the first comprehensive analysis of Michigan’s Swift and Sure Sanctions Probation Program (SSSPP), an alternative-to-incarceration program. The findings indicate that SSSPP participants had lower recidivism rates compared with individuals sentenced to probation-as-usual. Policy implications and suggestions for future research are offered.